PERTANGGUNG JAWABAN PIDANA ATAS KELALAIAN DIAGNOSA OLEH DOKTER HINGGA MENGAKIBATKAN KEMATIAN ANAK DALAM KANDUNGAN - Zola Agustina, Zola Agustina; Hariri, Achmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
Doctors are obliged to provide the best medical services for patients, this medical service can be in the form of delivering medical actions according to the medical service standards needed for the recovery of their patients, but sometimes the results achieved by the doctor are not as expected dDue to the lack of knowledge and skills of doctors which results in malpractice. a medical error made by a doctor) against a patient that results in fatal (disability and even death). People who are harmed by medical malpractice need legal protection that has caused further harm or suffering to patients. To establish a legal certainty and guarantee health care services and accommodate these needs, in addition to the KUHP, the government has issued a law in the field of health and a doctor's practice law, namely Law Number 23 of 1992 in conjunction with Law Number 36 of 2009 concerning Health. and Law Number 29 of 2004 concerning Doctor's Practice. This study has two formulations of the problem, namely: (1) How is a characteristic that does a problem in a medical procedure in a hospital? (2) What are the criminal responsibilities committed by the doctor for the crime? The research method used in this study is juridical-normative legal research so that it can obtain data that includes legal material in a primary and legal in a secondary manner.